Environmental influences on physical activity – Romanian youths' perspectives. (December 2018) - Sandu, Petru; Chereches, Razvan M.; Baba, Catalin O.; Revnic, Radu N.; Mocean, Floarea
Abstract: Despite the numerous benefits of physical activity (PA), the percentages of children and youth reaching the recommended PA levels are still low. Environmental attributes were shown to influence children and youth PA. The aim of this study was to explore the perceived influence of (built, social, school, community) environmental factors on youth (transportation, leisure time, school based) PA attitudes and behavior. We conducted 5 focus-group interviews in Cluj-Napoca, Romania; a number of 54 high-school students, 18–19 years old participated in the study. There is a preponderance of influence of the built environment, followed by social environment: family and friends on youth's PA attitudes and behavior. Lack of knowledge about community programs and school physical education/PA related culture and policy negatively influence students' reported PA attitudes and behavior. Personal motivation and feelings of enjoyment and self-efficacy can support youth PA. Local governments should adapt their public transportation policies; public and private providers should increase the visibility of PA programs targeting youth; schools should explore opportunities for developing active friendly culture/policies. Highlights: This is the first study using a socio-ecological model to explore the influence of environmental factors on LMIC youth PA. Built environment, public transportation and family & colleagues influence transportation related PA in youth. Proximity, quality, diversity and safety of LTPA infrastructure positively influence PA in youth. High-schools PA related culture/policy limit youth school based PA. PA promotion community programs targeting youth should be more diverse and better advertised. Social support for PA has to be backed-up by PA supportive built environments.